Clinical Profile and Outcome in Neonates and Pediatric Children with COVID-19 Infection at a Tertiary Care Center in South India - N. Madhavi; M. Madan Mohan; K. Jhansi Padma; V. Venkata Vijayalakshmi (Research Highlights in Disease and Health Research Vol. 8, 2023)
The present study shows that how the third wave of Covid 19 children were mostly asymptomatic or mild symptoms in both neonates and children with no significant increase in morbidity and mortality when compared to the previous waves of Covid. Covid 19 disease has been less severe in children causing fewer infections, severity, and deaths. The majority of affected children are asymptomatic (>70%) and in those symptomatic, the illness has been mild with <1.5% of children requiring hospitalizations. In order to understand the clinical, morbidity profile, and outcomes in neonates born to Covid positive mothers and children who are Covid positive, this study was conducted at a tertiary paediatric Covid care centre during the third wave. .Neonates born to Covid positive mothers and children between the age group 1 month to 12 years admitted in Government General Hospital, Kakinada, Andhra Pradesh from 1st January 2022 to 31st March 2022 were included in the study. Their demographic, clinical, morbidity profile, treatment details were noted and outcomes observed.All neonates were found to be RTPCR negative. The cause of respiratory distress in these newborns was prematurity, birth asphyxia, and meconium aspiration. Fever and gastrointestinal symptoms as seen in infected neonates in other studies were not present in this study. Similar findings were noted by NNF India Covid 19 registry. Prematurity, birth asphyxia and respiratory distress were the most presenting complaints. Four newborns died due to perinatal complications. Pediatric admissions were more in children less than 10 years with 15% of children being asymptomatic.Symptomatic children had fever, cough, and running nose as the most presenting complaints. Two children who had co-morbidities at the time of admission died. As routine vaccines like the measles vaccine have shown cross-protection against Covid 19 in some studies, routine vaccination of children should be strongly encouraged. It is necessary to monitor all Covid-infected kids, whether they are exhibiting symptoms or not, in order to look for long-term issues like MIS-C.